Climate change and economic growth prospects for Malawi: An uncertainty approach - Channing Arndt; Adam Schlosser; Kenneth Strzepek; James Thurlow (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Malawi confronts a development imperative in a context of rising temperatures and deep uncertainty about precipitation trends. We evaluate the implications of climate change for overall growth and development prospects to 2050. We focus on three impact channels: agriculture, road infrastructure, and hydropower generation while accounting explicitly for the uncertainty in climate forecasts. We find that climate change is unlikely to substantially slow overall economic growth over the next couple of decades. However, climate change implications become more pronounced over time and may become substantially more severe after 2050, especially if effective global mitigation policies fail to materialize.
Keywords: O1; O5; Q54; 330; Malawi; climate change; growth; development